LncRNA RP11-59J16.2 aggravates apoptosis and increases tau phosphorylation by targeting MCM2 in AD - Guan, Fulin; Gao, Qichang; Dai, Xinghua; Li, Lei; Bao, Rui; Gu, Jiaao (Frontiers in Genetics, 2022)
Objective Alzheimer's disease (AD) is a degenerative disease of the central nervous system with unclear pathogenesis, accounting for 60% - 70% of dementia cases. Long noncoding RNAs (LncRNAs) exerts functions in the development of AD. This study aims to explore the role of differentially expressed lncRNAs in AD patients' serum in the pathogenesis of AD. Methods Microarray analysis was performed in the serum of AD patients and healthy controls to establish lncRNAs and mRNAs expression profiles. SH-SY5Y cells were treated with Aβ 1-42 to establish an AD cell model. The expression of RP11-59J16.2 and MCM2 was determined by qRT-PCR. Dual-luciferase reporter gene analysis verified the targeting effect of RP11-59J16.2 on MCM2. Inhibition of RP11-59J16.2 or overexpression of MCM2, CCK-8, and flow cytometry was used to detect cell viability and apoptosis, and Western Blot was used to detect the expression of p-Tau. Results Differential expression of lncRNAs and mRNAs was screened by microarray data, and high expression of RP11-59J16.2 and low expression of MCM2 were detected in the serum of AD patients. GO analysis and KEGG pathway analysis revealed that the G1/S transition of the mitotic cell cycle may be involved in the development of AD. Dual-luciferase reporter gene analysis verified the targeted regulation of RP11-59J16.2 on MCM2. CCK-8 assay and Annexin V FITC/PI apoptosis assay kit results showed that RP11-59J16.2 could reduce cell viability, aggravate apoptosis, and increase Tau phosphorylation in the AD cell model by inhibiting MCM2. Conclusion Our study revealed a novel lncRNA RP11-59J16.2 that could promote neuronal apoptosis and increase Tau phosphorylation by regulating MCM2 in the AD cell model and indicated that lncRNA RP11-59J16.2 might be a potential target molecule for AD development.